AB0786 Role of calcium antagonists in the cancer of systemic sclerosis, an association under discussion. (12th June 2018) - Freire, M.; Cabaleiro, A.; Suarez, M.; Estevez, M.; Rodríguez, L.; Cacheiro, J.M.; Lorenzo, R.; Val, N.; Argibay, A.; Rivera, A.
Abstract : Background: The use of calcium channel blockers (CCB) is widespread in systemic sclerosis (SSc) for the treatment of Raynaud's phenomenon, present in 95% of patients. CCB can alter apoptosis, a mechanism for the destruction of cancer cells. In SSc the risk of cancer is increased, but the role that CCB can play is not clear, with contradictory data obtained so far. 1, 2 Objectives: To analyse the role of CCB in the appearance of cancer in a cohort of patients with systemic sclerosis. Methods: Encoded patients under the diagnosis of SSc in our hospital from 1985 until December of 2017 were collected. Medical records were reviewed, recording clinico-epidemiological data and treatments used. Results: 120 patients have been diagnosed of SSc (103 females, 17 males), 22 of whom (18, 3%) have developed cáncer. The type of cáncer were (in order of frecuency): breast (12 patients, 57%), gastrointestinal (4 patients, 33%), one hypernephroma, one endometrial carcinoma, one lyphoma, one skin cáncer and one epidermoid of tongue. Adenocarcinoma was the most frequently histologic pattern found (16 patients, 76%). Interestingly, the diagnosis of SSc was made at an older age in those patients diagnosed of cáncer (66, 4±11, 7 vs 54, 8±17, 3 years old, p=0, 019); An age older than 55 years old conferred a relative risk (RR) of cáncer of 1, 69 1, 26–2, 25 in the global cohort and a RR of 3, 26 1, 18–8, 99 in the female cohort. Although the association cancer and CCB did not reach statistical significance, the association CCB and female patients older tan 55 years elevate de RR of cáncer to 4, 16 (0.96–17, 95). All other characteristics (epidemioloical, clinical, analytical and another treatments) analized did not reach statistical significant differences. Conclusions: CCB increase in our series the risk of cancer in women over 55 yeras old. CCB could be implicated in the patogenia of cáncer in SSc. Due to the broad use of this in the SSc population, it may be require to study in a large number of patients in order to explore this association. References: [1] Colaci M, et al. Breast cancer in systemic sclerosis: Results of a cross-linkage of an Italian Rheumatologic Center and a population-based Cancer Registry and review of the literature. Autoimmunity Reviews2014, 13(2): 132–137 [2] Bernal-Bello D, et al. Novel risk factors related to cancer in scleroderma, Autoimmunity Reviews2017, doi: 10.1016/j.autrev.2017.03.012 Disclosure of Interest: None declared